2018
DOI: 10.1002/stc.2242
|View full text |Cite
|
Sign up to set email alerts
|

Damage quantification of beam structures using deflection influence lines

Abstract: Summary Influence lines (ILs) have recently been proposed as an emerging index for structural damage localization. This study investigated a novel damage detection and quantification method that is based on deflection ILs (DILs) for beam structures. By reconstructing DIL matrices using a matrix decomposition method, the relationship between structural damage and changes in DILs was revealed. Subsequently, a DIL‐based method was proposed to locate and quantify damage in beam structures. Numerical case studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…More recently, damage quantification methods have been proposed by using deflection influence lines (DILs). For example, Chen et al (2018) revealed the relationship between change in DIL and structural damage in an explicit form, and then developed a novel damage detection and quantification method. One disadvantage of this method is its dependence on an accurate finite element model (FEM), which brings extra difficulties and errors to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, damage quantification methods have been proposed by using deflection influence lines (DILs). For example, Chen et al (2018) revealed the relationship between change in DIL and structural damage in an explicit form, and then developed a novel damage detection and quantification method. One disadvantage of this method is its dependence on an accurate finite element model (FEM), which brings extra difficulties and errors to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with dynamic parameters‐based damage detection methods, influence coefficients‐based methods are insensitive to environmental parameters change and can be applied to local damage detection. From influence line to influence surface, traditional bridge influence line can only reflect the stiffness information of a certain section of the bridge 14,15 and can be employed for one‐dimensional bridge damage detection 16,17 . On the other hand, the bridge influence surface contains the bridge stiffness information of any point of the bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 20 used the empirical mode decomposition method to extract bridge influence line from dynamic response induced by high speed vehicle. Chen et al 16,21 then introduced the regularization penalty function to the least square method to reduce the unreasonable fluctuation in the identified result. Froseth et al 22 extracted bridge influence lines from the frequency domain and increased the computational efficiency by several orders of magnitude compared with the computational efficiency of a traditional time domain model.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is worth noting that in recent years, a damage identification method based on influence line changes has emerged . The definition of the influence line is shown as follows: When the unit concentrated load moves through the bridge in a perpendicular direction, the response curve for a certain point in a certain section is called influence line.…”
Section: Introductionmentioning
confidence: 99%